P425Single procedure pace and ablate. evaluation of efficacy and safety comparing three different vascular routes. (18th June 2020) - Abbas, M; Whittaker, L; Chapman, M; Thornley, A R; Towmey, D; James, S; Bates, M
Abstract: Funding Acknowledgements: No financial support for this study Introduction: Permanent pacemaker implantation combined with AVN ablation is a well-established treatment for rate control in patients with atrial fibrillation refractory to medical therapy. At the same sitting, this has been achieved in a single procedure via the subclavian vein (SCV) for both pacemaker implantation and AVN ablation, by pacemaker implantation via the SCV with femoral access for AVN ablation or by using the femoral vein (FV) for leadless pacemaker implantation and AVN ablation with a coaxial single-puncture technique. We evaluated all combined procedures (pacemaker implantation and AVN ablation at the same sitting) performed in a single centre over 9 years comparing clinical outcomes, complications rates and procedure times. Statistical methods: Continuous variables are described as mean ± standard deviation (SD), and statistical differences between groups were evaluated by one-way ANOVA. A X2 test was used for categorical variables, with Fisher's exact test for any field where the expected frequency was ≤5 with pvalue < 0.05 considered as statistically significant. The statistical analysis was performed using SPSS software package. Results: 141 patients underwent AVN ablation at our institution as part of a 'pace and ablate' single procedure strategy between 14/2/11 and 10/6/19. 61 patients had a combined procedure via the SCV, 66 patients had pacemaker implanted via the SCV and AVN ablation via the FV in the same sitting and 14 patients had leadless pacemaker (Micra) implantation and AVN ablation via the FV. Our findings suggest that the fluoroscopy time as well as the total catheter laboratory time were much less in the Micra group compared to the other groups. In the conventional pacemaker groups (group 1 and 2), the fluoroscopy time was not statistically different between the two. There was a trend towards acute procedural failure, switching to another access as well as a higher complication rate in the SCV group, however this has not reached statistical significance. Conclusion: Our early data suggests that pacemaker implantation and AVN ablation with a coaxial single femoral vein puncture technique is safe and takes less fluoroscopy time as well as total laboratory time.